2008
DOI: 10.1007/s12144-008-9025-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Failing to Give an Apology and the Need-for-Cognition on Anger

Abstract: This study examined how failing to give an apology would affect the anger of persons high and low in the need-for-cognition. We hypothesized that failing to apologize when there was an opportunity would lead to more anger than a no communication control condition, and that apologizing would lead to less anger than the control condition. Further, we hypothesized that these effects would be particularly strong in participants with a low need-for-cognition. To test these hypotheses 60 participants were put in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…These mixed findings may reflect the fact that apologies can be diverse in nature, and they can be given in different contexts with different meanings. Other studies investigating the effects of apologies have found that results tend to vary across different types of people and across different contexts (De Cremer, Pillutla, & Folmer, 2011;Thomas & Millar, 2008). It may be that further work needs to be done to clarify what people mean when they say they desire an apology, and to differentiate between different types of apologies and between different contexts.…”
Section: Discussionmentioning
confidence: 97%
“…These mixed findings may reflect the fact that apologies can be diverse in nature, and they can be given in different contexts with different meanings. Other studies investigating the effects of apologies have found that results tend to vary across different types of people and across different contexts (De Cremer, Pillutla, & Folmer, 2011;Thomas & Millar, 2008). It may be that further work needs to be done to clarify what people mean when they say they desire an apology, and to differentiate between different types of apologies and between different contexts.…”
Section: Discussionmentioning
confidence: 97%
“…Tomlinson et al also found that an apology with an internal attribution (the violator explicitly accepted responsibility for causing the violation) was found to be more effective than an apology with an external attribution (indicating that the violation was caused by 'bad luck' or other causes outside the violator's control). To further show the importance of an apology, other research has shown that no apology can actually lead to anger in the victim (Thomas and Millar, 2008). Finally, mixed reviews exist regarding when apologies should be offered: Frantz and Bennigson (2005) hypothesized and found support for the idea that later apologies are more effective since it shows the victim that the violator has had time to think about their transgression; Tomlinson et al (2004), however, found that a victim was more willing to accept trust repair efforts when they were made sooner after a trust violation.…”
Section: Question 9: If Parties Believe That Trust Can Be Repaired Tmentioning
confidence: 99%
“…Such apologies contained several elements that could be ordered along ''a continuum of completeness' ' (p. 276). Subsequent scholarship focused on additive elements that might influence the relationship between apology and outcome (Kim et al 2004;Scher and Darley 1997;Thomas and Millar 2008). For example, Lazare (2004) identifies various critical elements such as acknowledgment, timing, remorse, and reparations.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the wake of ever errant behavior by individual actors and organizational entities, apologies are increasingly viewed as an injunctive norm (Thomas and Millar 2008). Nonetheless, a study revealed that CEOs of major companies hardly ever apologize for managerial error (Finkelstein 2003).…”
Section: Introductionmentioning
confidence: 99%